Air quality and synergistic health effects of ozone and nitrogen oxides in response to China’s integrated air quality control policies during 2015–2019 - Zhang, Xuguo; Fung, Jimmy C.H.; Lau, Alexis K.H.; Hossain, Md Shakhaoat; Louie, Peter K.K.; Huang, Wei (Chemosphere (Oxford), 2021)
O3 pollution had been worsening in mainland China in the past decade, posing significant human health challenges. The NOx control would trigger increasing O3 concentrations in response to a series of released China emission reduction policies. This study used sensitivity analysis methodology to explore the effectiveness of integrated sectoral emission control policies that have been expanded throughout China. Air quality and synergistic health effects of O3 and NO2 were investigated to obtain an in-depth understanding of the O3 control, especially under a VOC-limited regime. The findings demonstrated that although the NOx-titration effect triggered an increase in O3, the combined health effects of two pollutants tended to improve in most regions of China under a VOC-limited regime. The region-based annual average NO2 concentrations exhibited a larger reduction in Hong Kong (HK) than in the Pearl River Delta Economic Zone (PRD EZ). The short-term measures led to substantial health benefits for Shenzhen and HK. The sectoral emission controls demonstrated a considerable health improvement for the major PRD EZ cities. Joint national control efforts confined the domain-wide health risks below the safety line in China. National cooperative efforts in China could avoid more than 1.5–2% of the emergency hospital admissions for cardiovascular and respiratory diseases attributed to NO2 and O3 exposure. The observed O3 increases due to the NOx-titration effect for calculating the integral health effects of emission control on concentration reduction called for simultaneously strengthened controls on both NOx and VOC in areas subject to a VOC-limited regime. [Display omitted] •Propose a novel sensitivity analysis method to assess the health co-benefits of O3 and NO2 in 2020.•The combined health effects tended to improve in most regions of China under a VOC-limited regime.•Control measures in the 13th Five-Year-Plan led to substantial health benefits for Shenzhen & HK.•Sectoral emission controls demonstrated a considerable health improvement for major PRD cities.•Joint-national controls confined the domain-wide health risks below the safety line in China.